Molecular docking study of the phytol and its derivatives against COX-2 induced inflammation: A combined density functional study - Islam, Muhammad Torequl; Ray, Pranta; Khalipha, Abul Bashar Ripon; Hafiz Hassan, SM; Khan, Md. Roich; Rouf, Razina (Recent Research in Science and Technology, 2020)
This study aimed to determine the activity of PYT and its derivatives against COX-2, including 5IKR protein induced inflammation by using the computational tools. PYT and its derivatives have been designed by utilizing density functional theory (DFT) and the performance of the drugs was also evaluated by molecular docking study. Results suggest that the NH2 derivative of PYT (D-NH2) showed binding energy -6.4 (Kcal/mol) with protein 5IKR of COX-2 compared to the main drug (D) that showed binding energy -5.1 (Kcal/mol) with the same protein. HOMO and LUMO energy values were also calculated to determine the chemical reactivity of all the modified drugs. Non-covalent interactions of PYT and its derivatives were essential in improving the performance. In conclusion, D-NH2 showed better preference in inhibiting to the protein 5IKR of COX-2 compared to other modified drugs and it can be claimed that D-NH2 will be the best conformer for COX-2 induced inflammation.